An Analysis of Interferences on English for Medical Purpose Speaking Activity - Muhammad Rudy; Nur Arifah Drajati (Aksara: Jurnal Bahasa dan Sastra, 2017)
One of impacts that can be observed on language difference during learning English is interference. Indonesian medical students have problem with speaking; what they said does not reflects what was in their mind. This descriptive analysis study identified the interference on medical students while doing speaking activity in the class. Four students were chosen randomly as the subjects to give their diagnosis verbally. Their speaking was recorded, transcribed and coded. The analysis was done on basis of four types of interference by categorizing language transfer into four types: phonological, grammatical, lexical and orthographical. Result showed that among four language transfers or interferences, phonological and grammatical interferences were prominent. As addition generalization and fossilization can be observed. Students did less English pronunciation practice in the class meanwhile Indonesian language has very different way on pronouncing a word. Some medical terms such as LDL and hypertension were uttered in Indonesian language within giving diagnosis in English. Teachers at Medical Class should introduce medical terms in English together with the pronunciation. The pronunciation recital should be scheduled before speaking activity. DOI: http://dx.doi.org/10.23960/aksara/v18i2.pp133-144